2021
DOI: 10.1042/etls20210129
|View full text |Cite
|
Sign up to set email alerts
|

Practical considerations for delivering on the sustainability promise of fermentation-based biomanufacturing

Abstract: Increasingly, bio-based products made via sugar-powered microbial cell factories and industrial fermentation are reaching the market and presenting themselves as sustainable alternatives to fossil and animal-based products. The sustainability potential of biotechnology, however, has been shown to come with trade-offs and cannot be taken for granted. Shared environmental impact hotspots have been identified across industrial fermentation-based products, including biomass production, energy consumption, and end-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Commercial investment in "brewed materials" and "engineered living materials" underscores the high current interest in engineered protein biomaterials. [1,4,60] Whilst the last decade has seen progress in expressing silk proteins, [10,11,29,38,61] modifying their sequences, [32,62,63] and developing biomimetic processing workflows, [31,47] the notion that microbes could autonomously synthesize, secrete, and process protein materials has not been widely discussed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Commercial investment in "brewed materials" and "engineered living materials" underscores the high current interest in engineered protein biomaterials. [1,4,60] Whilst the last decade has seen progress in expressing silk proteins, [10,11,29,38,61] modifying their sequences, [32,62,63] and developing biomimetic processing workflows, [31,47] the notion that microbes could autonomously synthesize, secrete, and process protein materials has not been widely discussed.…”
Section: Discussionmentioning
confidence: 99%
“…Protein‐based biomaterials have recently attracted attention because of their multifaceted uses in biomedical applications as well as emerging applications as a sustainable material [1–4] . Like other biomaterials, proteins tend to be biocompatible and biodegradable, though they are also genetically‐encodable and programmable [5] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…From a material perspective, this project delves into the artistic potential of biodesign and, specifically, into the interaction between the different bio-composite materials that constitute the research outcome in order to exact form. While biomaterial production offers a vast array of sustainable avenues, current research is prominent in performance, science-based biotechnology and replacing non-renewable materials (Lips, 2021;Parkes, 2021), while the creation of designerly or artistically-oriented biomaterials occupies a more inconspicuous position (Doveil, 2022). Observing this research gap in parallel with the struggles of practice-based design and artistic expression in establishing their disciplinary validity within academia (Tonkinwise, 2017), it can be concluded that artistic research foundations in conjunction with scientific and biotechnological workflows may aid in legitimising the intersection between science and design as a practice field.…”
Section: Introductionmentioning
confidence: 99%
“…From a material perspective, this project delves into the artistic potential of biodesign and, specifically, into the interaction between the different bio-composite materials that constitute the research outcome in order to exact form. While biomaterial production offers a vast array of sustainable avenues, current research is prominent in performance, science-based biotechnology and replacing non-renewable materials (Lips, 2021;Parkes, 2021), while the creation of designerly or artistically-oriented biomaterials occupies a more inconspicuous position (Doveil, 2022). Observing this research gap in parallel with the struggles of practice-based design and artistic expression in establishing their disciplinary validity within academia (Tonkinwise, 2017), it can be concluded that artistic research foundations in conjunction with scientific and biotechnological workflows may aid in legitimising the intersection between science and design as a practice field.…”
Section: Introductionmentioning
confidence: 99%